2017
DOI: 10.1155/2017/1767198
|View full text |Cite
|
Sign up to set email alerts
|

Apple Flavonoids Suppress Carcinogen‐Induced DNA Damage in Normal Human Bronchial Epithelial Cells

Abstract: Scope Human neoplastic transformation due to DNA damage poses an increasing global healthcare concern. Maintaining genomic integrity is crucial for avoiding tumor initiation and progression. The present study aimed to investigate the efficacy of an apple flavonoid fraction (AF4) against various carcinogen-induced toxicity in normal human bronchial epithelial cells and its mechanism of DNA damage response and repair processes. Methods and Results AF4-pretreated cells were exposed to nicotine-derived nitrosamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
(64 reference statements)
1
29
0
Order By: Relevance
“…It has been shown that antioxidants may protect DNA from H 2 O 2 -mediated damage, however some may actually escalate oxidative damage caused by H 2 O 2, or may even be genotoxic themselves [34] , [35] . The comet assay, a useful method for detecting DNA strand breaks at the single-cell level, has been used by us to study the impact of exogenous GSH and catechins on DNA integrity in both mentioned situations.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that antioxidants may protect DNA from H 2 O 2 -mediated damage, however some may actually escalate oxidative damage caused by H 2 O 2, or may even be genotoxic themselves [34] , [35] . The comet assay, a useful method for detecting DNA strand breaks at the single-cell level, has been used by us to study the impact of exogenous GSH and catechins on DNA integrity in both mentioned situations.…”
Section: Resultsmentioning
confidence: 99%
“…The biological effects of apple phenolic compounds are also of interest. Flavonoids extracted from apple peel were implicated in the suppression of breast cancer and the growth of carcinogenic cells in the bronchi [George & Rupasinghe, 2017;Loung et al, 2019]. In turn, Zielińska et al [2019] proved the potential benefits of apple-derived polyphenols in modulating inflammation at the intestinal level.…”
Section: Apple Phenolic Compounds -The Biological Effectsmentioning
confidence: 98%
“…Pretreatment with AF4 reduced the ROS level with an increase in anti-oxidant enzymes. Further, AF4 reduces DNA damage and enhanced protection against carcinogens by facilitating DNA repair mechanisms [168]. A study by Kaewmool et al, showed both anti-inflammatory and apoptotic effects of C3G in PC-12 cells.…”
Section: Cyanidinmentioning
confidence: 98%